Scabies: epidemiology, diagnosis, and treatment - Cord Sunderkötter; Johannes Wohlrab; Henning Hamm (2021)
Scabies is a skin infestation whose incidence is apparently rising.This review is based on pertinent articles retrieved by a selective search of PubMed on diagnosis and treatment strategies.Thread-like papules (burrows), new, intense pruritus, and dermatitis guide the suspected diagnosis which is confirmed by the microscopic or dermatoscopic demonstration of scabies mites. The first line therapy is topical application of permethrin, in accordance with the current recommendations for its use. Other treatment options include systemic ivermectin and topical crotamiton or benzyl benzoate. A combination of permethrin and ivermectin is used to treat otherwise intractable cases and is generally indicated for the treatment of crusted scabies. Known causes of treatment failure include improper application of the external agents, failure of repeated treatment with ivermectin, incomplete decontamination of furnishings and clothes, failure to simultaneously treat contact persons, absence of written documents explaining treatment modalities, and the patient's belonging to a risk group. Even though there has not yet been any direct proof of resistance of scabies mites to permethrin, there is a rising number of welldocumented cases of poor response to this agent. Moxidectin is a new substance now undergoing clinical testing.Treatment of scabies according to the guidelines and the additional recommendations reported here should result in effective curing, even in cases that are thought to be intractable.